2023
DOI: 10.1002/ijc.34648
|View full text |Cite
|
Sign up to set email alerts
|

Association between antibiotic use during early life and early‐onset colorectal cancer risk overall and according to polygenic risk and FUT2 genotypes

Fangyuan Jiang,
Daniel Boakye,
Jing Sun
et al.

Abstract: Early‐onset colorectal cancer (EOCRC) has been increasing worldwide. Potential risk factors may have occurred in childhood or adolescence. We investigated the associations between early‐life factors and EOCRC risk, with a particular focus on long‐term or recurrent antibiotic use (LRAU) and its interaction with genetic factors. Data on the UK Biobank participants recruited between 2006 and 2010 and followed up to February 2022 were used. We used logistic regression to estimate adjusted odds ratios (ORs) and 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…determined that antibiotics increased EOCRC risk (OR = 1.49, 95% CI 1.07–2.07) after investigating 7,903 CRC cases and 30,418 controls in their US cohort. Further, a study of the UK biobank which is comprised of 113,256 participants ( n = 165 EOCRC cases, n = 719 early‐onset colorectal adenoma cases), found that long‐term or recurrent courses of antibiotics (≥ 3/year) were associated with increased EOCRC risk (OR = 1.48, 95% CI 1.01–2.17, p = 0.046) and adenomas (OR = 1.40, 95% CI 1.17–1.68 , p < 0.001) 15 . The discrepancies between these studies are likely due to the geographical influence on infection prevalence, local sensitivities and resistances, and antimicrobial stewardship between countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…determined that antibiotics increased EOCRC risk (OR = 1.49, 95% CI 1.07–2.07) after investigating 7,903 CRC cases and 30,418 controls in their US cohort. Further, a study of the UK biobank which is comprised of 113,256 participants ( n = 165 EOCRC cases, n = 719 early‐onset colorectal adenoma cases), found that long‐term or recurrent courses of antibiotics (≥ 3/year) were associated with increased EOCRC risk (OR = 1.48, 95% CI 1.01–2.17, p = 0.046) and adenomas (OR = 1.40, 95% CI 1.17–1.68 , p < 0.001) 15 . The discrepancies between these studies are likely due to the geographical influence on infection prevalence, local sensitivities and resistances, and antimicrobial stewardship between countries.…”
Section: Resultsmentioning
confidence: 99%
“…There is a significant overlap in the non-modifiable risk factors of EOCRC with LOCRC. For example, in their 2023 systematic review and meta-analysis of 36 studies which included 66,312 participants, Hua et al 6 identified that being male (odds ratio [OR] = 1.20, 95% CI 15 The discrepancies between these studies are likely due to the geographical influence on infection prevalence, local sensitivities and resistances, and antimicrobial stewardship between countries.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Regarding the effect of the therapeutic use of antibiotics during childhood, use which has been etiopathogenetically associated with a multitude of morbid conditions in later adult life ( e.g., inflammatory bowel disease). Jiang et al [ 47 ] found that long-term or recurrent antibiotic use by early life span is associated with an increased risk of early-CRC and adenomas and that the association with adenomas was significantly greater among individuals with the rs281377 TT/CT genotype. However, further studies are needed to investigate how long-term or recurrent antibiotic use contributes (together with genetic factors) to the modification of early-CRC risk, especially regarding the microbiome-related pathway that governs colon carcinogenesis.…”
Section: Etiopathogenetic Factorsmentioning
confidence: 99%